2016
DOI: 10.1177/0748730415625510
|View full text |Cite
|
Sign up to set email alerts
|

Chronotype, Light Exposure, Sleep, and Daytime Functioning in High School Students Attending Morning or Afternoon School Shifts

Abstract: Adolescent maturation is associated with delays of the endogenous circadian phase. Consequently, early school schedules may lead to a mismatch between internal and external time, which can be detrimental to adolescent sleep and health. In parallel, chronotype is known to play a role in adolescent health; evening chronotype adolescents are at higher risk for sleep problems and lower academic achievement. In the summer of 2008, Kénogami High School (Saguenay, Canada) was destroyed by fire. Kénogami students were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
47
2
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(53 citation statements)
references
References 61 publications
(98 reference statements)
2
47
2
2
Order By: Relevance
“…However, to our knowledge, only one study by Martin et al . () reported mean MESC scores according to their school shift. Mexican adolescents from the morning shift were more morning oriented, and adolescents from the afternoon shift were more evening oriented ( M = 28.27, SD = 4.58; M = 24.06, SD = 5.09, respectively) compared to Canadians from the morning shift and from the afternoon shift ( M = 27.6, SD = 1.0; M = 26.9, SD = 0.9, respectively).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, to our knowledge, only one study by Martin et al . () reported mean MESC scores according to their school shift. Mexican adolescents from the morning shift were more morning oriented, and adolescents from the afternoon shift were more evening oriented ( M = 28.27, SD = 4.58; M = 24.06, SD = 5.09, respectively) compared to Canadians from the morning shift and from the afternoon shift ( M = 27.6, SD = 1.0; M = 26.9, SD = 0.9, respectively).…”
Section: Discussionmentioning
confidence: 99%
“…As a result, the students were relocated to another school, and because of the limited number of classrooms available, morning and afternoon school schedules were implemented. This provided a novel opportunity to analyse these dual school shifts, which were nonexistent in Canada (Martin, Gaudreault, Perron, & Laberge, ). The study reported that afternoon students had longer sleep duration, less sleepiness, and lower light exposure than morning students – reporting the same results as the aforementioned studies.…”
Section: Introductionmentioning
confidence: 99%
“…In general, sleep duration was significantly longer for students attending the afternoon shifts. This was observed even in morning types who also reported higher sleepiness during the morning shift (Martin et al, ). Although the sample of students was small ( N = 57), the authors found no significant difference in grades between students attending the morning and the afternoon shift, and overall evening types did not obtain lower grades compared to morning types.…”
Section: How To Remove the Chronotype “Handicap”mentioning
confidence: 92%
“…Two other studies have assessed differences in sleep between high school students attending morning or afternoon lectures, taking chronotype into account (Koscec, Radosevic-Vidacek, & Bakotic, 2013;Martin, Gaudreault, Perron, & Laberge, 2016). In general, sleep duration was significantly longer for students attending the afternoon shifts.…”
Section: Delaying School Starting Timesmentioning
confidence: 99%
“…In field-based sleep and circadian studies, light exposure is currently widely measured using wrist-worn devices (e.g., [6][7][8][9][10]), due to their convenience and availability. GENEActiv devices are an affordable tool commonly used for this purpose, with 37 studies since 2014 having used the device's light outputs (Google Scholar search terms "GENEActiv"+"light"+"lux" or "GENEActiv"+"light"+"lx").…”
Section: Introductionmentioning
confidence: 99%